Use of a Partially Hydrolyzed 100% Whey-Based Infant Formula with Lactobacillus Reuteri in Infants with Caregiver-Perceived Intolerance - M. Czerkies Laura; L. Finn Kristen; D. Kineman Brian; A. Reichert Heidi; S. Cohen Sarah; S. Carvalho Ryan (Journal of Pediatric Health And Nutrition, 2019)
This study evaluated the impact of switching exclusively formula-fed infants with caregiver-perceived formula intolerance to a reduced lactose, partially hydrolyzed 100% whey-based formula (PHF-W) with Lactobacillus reuteri and 2-fucosyllactose. Infants identified as ‘very’ or ‘extremely’ fussy by caregivers were eligible for this single-arm, single-blind study. Subjects switched their current formula to study formula for three weeks. Gastrointestinal tolerance was assessed by the Infant Gastrointestinal Symptom Questionnaire (IGSQ) at baseline and end of the study. Caregivers ranked their infants’ fussiness (not at all, slightly, moderately, very, extremely) after the first three feedings of study formula and 24 hours after enrollment. A paired t-test was used to compare the change in IGSQ score, and a paired t-test and Wilcoxon signed rank test were used to compare post-feeding fussiness scores to baseline. Fifty infants (mean±std age 28.9±14.5 days) were enrolled; 41 completed the study per protocol. Mean (±std) baseline IGSQ score was 34.9±10.0, dropping to 22.1±7.5 after three weeks (p < 0.001). 48/50 (96%) caregivers stated their infants’ fussiness improved after 24 hours, and 2 (4%) remained the same. 42/46 (91%) caregivers stated their infants’ fussiness improved after the first feeding, and 4 (9%) remained the same. Caregiver-ranked fussiness significantly improved after the first, second, and third feedings and after 24 hours as compared to baseline (p < 0.001 for all). IGSQ scores significantly improved after three weeks of feeding with PHF-W containing Lactobacillus reuteri and 2-fucosyllactose in infants with caregiver-perceived intolerance, and improvements in fussiness were noted as quickly as after the first feeding.
Keywords: Lactobacillus reuteri